Implementation of Digital Records Management to Support Excellent Service at Vocational High Schools - Eka Yulianta (CV. Edujavare Publishing, 2026)
In the digital era, technological transformation has penetrated almost every sector, including archives management. The purpose of this study is to examine a digital-based archives management system that offers significant benefits, such as saving storage space, ease of searching and retrieving documents, and increased security through encryption technology. The research method used is a qualitative approach with a case study design, utilizing data collection techniques such as observation, interviews, and documentation. The results show that the implementation of a digital archives management system improves the speed of information access, data security, and accuracy in archives management compared to conventional systems. In addition, archive digitization contributes to improving the quality of administrative services for students, teachers, and external parties, characterized by faster responses, information transparency, and ease of document retrieval. However, this implementation still faces several challenges, such as limitations in technological infrastructure, human resource competency, and the lack of integrated standard operating procedures.